Temporal variability and environmental availability of inorganic constituents in an Antarctic marine sediment core from a polynya area in the Ross Sea - Malandrino Mery; Mentasti Edoardo; Giacomino Antonia; Abollino Ornella; DINELLI, ENRICO; SANDRINI, SILVIA; TOSITTI, LAURA (Toxicological & Environmental Chemistry, 2010)
In this paper vertical profiles of radionuclides, geochemical components and metals in a surface sediment core from the Ross Sea, Antarctica are presented. Tecniques applied include ICP-MS, AAS, XRF and High resolution gamma ray spectrometry. Correlation of data obtained and interpretation of vertical distribution is provided. The data are relevant to the biogeochemical cycling of elements in the Antarctic polynya of coastal Ross sea were important connection between atmosphere and the ocean control the marine food chain within a framework of global climatic connections